The 2002 Bali Bombing and the New Public Sphere: The Portrayal of Terrorism in Indonesian Online Discussion Forums - Sunesti, Yuyun (Al-Jamiah Research Centre, 2014)
This article examines heroic conceptions of terrorists, support, and sympathy for terrorism in Indonesia by undertaking a content analysis of four Indonesian online discussion forums in the aftermath of the 2002 Bali bombing. It is argued that online discussion forums are a particularly appropriate source of data from which to analyse Indonesiansâ perceptions of the bombers, as these forums are widely thought to be representative of a new public sphere that allows for political debate and participation. From discussions between July 2008 and January 2009, the article outlines how the bombers were constructed as heroes and anti-heroes by different members of different forums. Drawing on a cultural sociological perspective, the article highlights the importance of understanding the reputation of individual terrorists, and the influence of established heroic types in understanding contemporary conflict in Indonesian society.[Artikel ini membahas konsepsi kepahlawanan teroris, dukungan, dan simpati terhadap terorisme di Indonesia dengan melakukan analisis isi terhadap forum diskusi online terkait dengan peristiwa Bom Bali tahun 2002. Diasumsikan bahwa forum diskusi online merupakan sumber yang memadai untuk melihat persepsi masyarakat Indonesia mengenai pelaku pengeboman, karena forum seperti ini cukup dipercaya sebagai perwakilan ruang publik baru memungkinkan terjadinya keterlibatan dan debat yang bersifat politik. Dari diskusi yang terjadi antara Juli 2008 sampai Januari 2009, tergambar dalam artikel ini bahwa para pelaku pengeboman dikonstruksikan sebagai seorang pahlawan sekaligus sebagai musuh dalam forum yang berbeda. Dengan perspektif sosial-budaya, tulisan ini menggaris-bawahi pentingnya pemahaman terhadap reputasi masing-masing teroris dan pengaruh tipologi kepahlawanan dalam memahami konflik di tengah masyarakat Indonesia saat ini.]